(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: Proper feeding practices are essential for attaining and maintaining optimum nutrition, health, and development of infants and children. Exclusive breastfeeding during the first six months of life and continued breastfeeding for two years, together with age-appropriate, nutritionally adequate complementary feeding initiated after six months of age, are optimum Infant and Young Child Feeding (IYCF) practices. However, often many aspects of infant and young child feeding practices are not optimum, with serious consequences for the child. Objective: To determine the impact of Infant and Young Child Feeding (IYCF) practices on the nutritional status of children. Materials and Method: This Cross-sectional descriptive type of study was conducted among 314 children from 6 months to 24 months of age at the Pediatric Outpatient Department and EPI center of Rajshahi Medical College Hospital during the period of January 2017 to December 2018. Collected data were analyzed by using ’SPSS version 16. Result: Among 314 children exclusive breastfeeding (EBF) rate was 68.2% for the first six months, and timely started complementary feeding was 58.5% of cases. In 214 exclusive breastfed infants, only 4.7% and 1.4% of children were moderate to severely wasted and stunted, respectively. On the other hand, among 97 infants who were not exclusively breastfed, the percentage of moderate to severe wasting and stunting was 11.4% and 13.4%, respectively. Among the 175 timely started complementary feeding children, only 12% and 6% were moderate to severely underweight and wasted, respectively, no one was stunted, but among the inappropriately started complementary children, 20.2%, 12.5%, and 12.8% were moderately to severely underweight, wasted and stunted respectively. Conclusion: Most of the children who were given exclusive breastfeeding in the first six months and started complementary food at an appropriate time after six months had normal nutritional status. Both moderate to severe stunting and wasting were common in those children who were non-exclusively breastfed and started complementary feeding either early or late. TAJ 2022; 35: No-2: 83-91